A comparison of picture and GIF‐based preference assessments for social interaction. Issue 3 (21st January 2020) - Morris, Samuel L.; Vollmer, Timothy R.
Abstract : Researchers have recently begun to evaluate video‐based preference assessments; however, only two studies have evaluated the efficacy of this preference assessment modality in assessing preference for social interactions. Four individuals diagnosed with autism spectrum disorder who could not match pictures or graphic‐interchange‐format images (GIFs) of social interactions to in vivo interaction participated. We compared picture and GIF‐based paired‐stimulus preference assessments for social interaction and evaluated the preference assessment hierarchies by conducting a concurrent‐operant reinforcer assessment including all social interactions. The GIF‐based preference assessment produced similar hierarchies to the reinforcer assessment for all participants, whereas the picture‐based preference assessments produced similar hierarchies to the reinforcer assessment for 2 of 4 subjects. Additionally, we conducted a modality preference assessment in which we evaluated participants' preference for viewing GIFs or pictures of social interactions, and found that 3 out of 4 subjects displayed a preference for GIFs.